Debate on Patriarchal Interpretation of Hadith: An Overview - Hamisan@Khair, Nur Saadah (Al-Basirah Journal, 2021)
The criticism on Hadith as one of the legal sources in Islam is continually debating until the present day. For certain reasons, the Hadith has been disregarded as an infallible source, and its authenticity often becomes the subject of argument among the past and present scholars. One of the important debates in the study of Hadith is the existence of misogynistic traditions which are claimed to be found in the authentic Hadith collections. This paper aims to discover how the hadith has been criticized for being influenced by patriarchal interpretation and prejudiced as anti-women as claimed by the feminists. It is due to the male domination in major aspects of the Islamic texts, including the process of transmission, preservation, publication as well as interpretation. Unfortunately, the interpretation of the Hadith particularly those pertaining to women contains gender bias and discrimination against women. The feminists argue those Hadiths were interpreted in favor of men’s interests and patriarchal culture. In addition, this study also attempts to examine some reasons for rejecting the patriarchal interpretation as initiated by the feminists, with their aim to reject anti-women discourse and to emphasize the women-friendly interpretation of the Islamic texts. The finding shows that patriarchal interpretation might be the reason for mistreatment towards women, however, the Hadith contains divine wisdom equally for both genders. It is a mutual responsibility to provide a better understanding of the Hadith textually and contextually.